Visualisasi Desain Karakter Tokoh Utama dalam Lakon Wiracarita Batara Kamasara - A. K. Patra; Arthur S. Nalan; Supriatna Supriatna (Pascasarjana ISBI Bandung, 2022)
The existence of the Wangsakerta Manuscript phenomenon is an indication and source of data to be followed up as ideas or ideas in writing (story script) and visual works. The story script or the play contains pseudo fiction with a colossal nuance typical of the archipelago which was inspired by a fragment of the Sargah I Parwa I Wangsakerta Manuscript about the Nirleka era in Tatar Parahyangan. The issues raised were the issue of the existence and power conflict between the stealth clan and the human clan which led to war. Moving on from this, the creation work is entitled “Wiracarita Batara Kamasara”. This story tells about the struggle and heroism of a young man named Kamasara in fighting tyranny and evil, beside the mission to restore his Kabuyutan honor which has been destroyed by the demon clan. Actualizing this invention is through a qualitative method including field observation and literature studies. Anthropologically, the theoretical study used in this study is hermeneutic conception promoted by Paul Ricoure regarding Metaphor. The result of the manuscript analysis is then applied to visualize the character designs of the storyline in this epic play.Keywords: Wangsakerta Manuscript, Hermeneutics, Epic, Visualization of Character Design.